2018
DOI: 10.12688/wellcomeopenres.10352.3
|View full text |Cite
|
Sign up to set email alerts
|

The overlap between miscarriage and extreme preterm birth in a limited-resource setting on the Thailand-Myanmar border: a population cohort study

Abstract: Background : No universal  demarcation of gestational age  distinguishes miscarriage and stillbirth or extreme preterm birth (exPTB). This study provides a synopsis of outcome between 22 to <28 weeks gestation from a low resource setting. Methods : A retrospective record review of a population on the Thailand-Myanmar border was conducted. Outcomes were classified as miscarriage, late expulsion of products between 22 to < 28 weeks gestation with evidence of non-viability (mostly ultrasound absent fetal heart be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“… a Pregnancy outcome before 28 weeks of gestation was considered as a miscarriage [ 28 ]. b Demographic characteristics of pregnant women not contacted or who declined were similar to that of pregnant women counselled and interested except for a higher proportion of smokers (13.1% (100/768) vs 9.9% (184/1860), p = 0.019).…”
Section: Resultsmentioning
confidence: 99%
“… a Pregnancy outcome before 28 weeks of gestation was considered as a miscarriage [ 28 ]. b Demographic characteristics of pregnant women not contacted or who declined were similar to that of pregnant women counselled and interested except for a higher proportion of smokers (13.1% (100/768) vs 9.9% (184/1860), p = 0.019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we are aware that the number of births at this particular gestational week may be underestimated because many hospitals in rural areas of Thailand consider ending of pregnancy at this gestation as a spontaneous abortion. A population cohort study of extremely preterm births on the Thailand‐Myanmar border showed that delivery between 22 and <28 weeks of gestation occurred in 0.9% (472/49931) and a neonatal mortality rate approached 100% …”
Section: Discussionmentioning
confidence: 99%
“…A population cohort study of extremely preterm births on the Thailand-Myanmar border showed that delivery between 22 and <28 weeks of gestation occurred in 0.9% (472/49931) and a neonatal mortality rate approached 100%. 19 A study of a survival rate to hospital discharge in a university hospital in Muscat, Oman, between 2006 and 2013 revealed that, of a total of 81 infants between 23 and 26 gestational weeks admitted to the NICU, the survival rate of infants born at 23 weeks' gestation was 12.5% compared to 33.3% and 72.4% of those born at 24 and 25 weeks' gestation, respectively. 20 In our study, infants born at 24 weeks' GA had an approximately 50-65% composite chance of death or survival with a major disability.…”
Section: Discussionmentioning
confidence: 99%
“…Stillbirth was defined as birth of a fetus with no signs of life, at a gestation of ≥28 +0 weeks. SMRUs definition for stillbirth follows that recommended by WHO for international comparison and the rationale for the miscarriage definition, which has no agreed international standard, is provided elsewhere [ 23 ]. Preterm birth (PTB) was defined as pregnancy outcome between 28 +0 and 37 +0 weeks of gestation; only cases with their first ANC contact before completion of 37 weeks of gestation were considered for this analysis.…”
Section: Methodsmentioning
confidence: 99%